Validasi Instrumen Evaluasi Kinerja di PT DUNKIN DONUT dengan menggunakan Metode Balance ScoreCard - Maesyaroh Rasyid; Diana Niati Manalu; Syamsul Hidayat (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Goals Performance measurement is a process used to assess the extent to which an individual or organization has achieved the goals that have been set. Existing research explains the relationship between price, promotion, satisfaction, and loyalty, but many aim to explore one aspect without considering the dynamics of the interaction between price and promotion. In some contexts, lower prices are not always matched by high levels of satisfaction, indicating the need for further research. The Balanced Scorecard method can also be used to measure company performance. PT Dunkin Donat is a private company operating in the well-known food and beverage sector. To be able to have an advantage in rapid business competition, PT Dunkin Donat Unggul needs to have an appropriate performance measurement system framework. The following are the research results: 1). Service: The service provided by Dunkin Donuts is considered quite good for consumer needs, 2). Facilities: the facilities provided to consumers are considered quite good in terms of cleanliness and comfort, 3). Menu: the menu served by Dunkin Donuts is quite good because there are various types of menus that suit consumer tastes, dan 4). Appearance: the appearance of Dunkin Donuts employees is quite good because they look attractive so that consumers feel comfortable.